Impact of 2.5 mg versus 5 mg letrozole co-treatment in an antagonist protocol for IVF: a retrospective study - Lin, Jing; Wu, Fenglu; Zhang, Kai; Zhu, Yanwen; Wang, Bian; Zhu, Qianqian; Lin, Jiaying (Frontiers in Endocrinology, 2023)
Objective: The present study aimed to compare the effectiveness of two different doses of letrozole (2.5 mg and 5 mg daily) in an antagonist protocol for infertile women with normal ovarian reserve. Methods: This retrospective cohort study included infertile women who underwent in vitro fertilization treatment with letrozole co-treatment at doses of 2.5 mg and 5 mg from 2007 – 2021 at Shanghai Ninth People’s Hospital (Shanghai, China). The control group comprised infertile women who received gonadotropin-releasing hormone antagonist alone. The primary outcome was the cumulative live birth rate, while secondary outcomes included follicular phase endocrine parameters, ovarian stimulation outcomes, pregnancy outcomes, and incidences of maternal and neonatal complications. Baseline and follow-up data were compared between the groups using ANOVA for normally distributed variables, the Kruskal-Wallis test for non-normally distributed variables, and the Chi-square test for categorical variables. Results: A total of 422 participants were enrolled in the study, with 211 women in the antagonist group, 109 women in the 2.5 mg letrozole co-treatment group, and 102 women in the 5 mg letrozole co-treatment group. Letrozole co-treatment significantly suppressed oestradiol and follicle-stimulating hormone concentrations from stimulation day 5 and onwards, while increasing luteinizing hormone levels on stimulation day 5 and trigger day. The effect was more pronounced with a 5 mg dose of letrozole compared to a 2.5 mg dose (P < 0.05). Administration of 5 mg letrozole reduced the gonadotropin dose (P < 0.05) without negatively affecting the number of oocytes retrieved and subsequent embryo parameters (P > 0.05). The analysis of cumulative live birth rates showed rates of 29.4% in the letrozole 5 mg group, 27.5% in the letrozole 2.5 mg group, and 33.6% in the control group, with no statistically significant difference (P > 0.05). There were no reported pregnancy complications in the two letrozole groups. Additionally, there were no significant differences among the three groups in terms of gestational age and birth weight for both singleton and twin births. Conclusion: This study indicates that the administration of letrozole in an antagonist protocol, at both 2.5 mg and 5 mg dosages, results in comparable similar clinical outcomes.